1978
DOI: 10.1159/000237784
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Metabolism of Talampicillin

Abstract: Talampicillin is an ester of ampicillin which is readily hydrolysed on absorption to release ampicillin. It is well absorbed from the gastro-intestinal tract resulting in a greater bioavailability of ampicillin than can be achieved with equivalent doses of ampicillin itself. Dose response studies have confirmed a direct relationship between the dose of talampicillin administered and peak serum ampicillin concentration and urinary excretion of ampicillin. Dosing of ampicillin after food has been shown to advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
3
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The serum concentrations found in this study are, in general, compatible with previous reports (4)(5)(6)(7)(8). The coefficient of variation in individual peak serum concentrations of approximately 20% after all doses is in agreement with previous results with bacampicillin (7,8), pivampicillin (8), and talampicillin (9), verifying a uniform and reliable absorption of these prodrugs.…”
supporting
confidence: 92%
“…The serum concentrations found in this study are, in general, compatible with previous reports (4)(5)(6)(7)(8). The coefficient of variation in individual peak serum concentrations of approximately 20% after all doses is in agreement with previous results with bacampicillin (7,8), pivampicillin (8), and talampicillin (9), verifying a uniform and reliable absorption of these prodrugs.…”
supporting
confidence: 92%
“…A decrease in the Cmax and a delay in the Tmax have been shown; however, AUC and urinary recovery were not reduced significantly (6)(7)(8)12). It is therefore considered that the bioavailability of talampicillin is not changed by food (6)(7)(8). Bacampicillin is also not considered to be affected by food (10).…”
mentioning
confidence: 98%
“…It has been observed that the absorption of pivampicillin is reduced when it is administered with a standard breakfast consisting of dairy products as well as eggs, sausage, toast, and milk, resulting in decreased AUC by almost half compared with that obtained in a fasting state (4). The interaction of talampicillin with food has also been well studied (6)(7)(8)12). A decrease in the Cmax and a delay in the Tmax have been shown; however, AUC and urinary recovery were not reduced significantly (6)(7)(8)12).…”
mentioning
confidence: 99%
See 1 more Smart Citation